A formação superior em Direito na obra de Machado de Assis - Calabresi, Luis Henrique de Freitas (2008)
Machado de Assis's literary production is closely related to the society of its time and can contribute greatly to the understanting of XIX century Brazil. In this dissertation we used the works of Machado de Assis in the field of History of Education. We analysed the higher education in law during XIX century though the novels Dom Casmurro and Memórias Póstumas de Brás Cubas. The choice of higher education in law justifies itself due to the predominance that this course achieved in that historical period. The choice of the Machado de Assis's novels mentioned above was due to the characteristics of its narrators, Dom Casmurro and Brás Cubas, as being law school graduates, and also because of several references to law studies throughout these works. We analyzed these novels as our primary sources, selecting excerpts related to our theme and comparing them with historical studies, law school studies and critical studies on Machado the Assis's works as well. We have found in Dom Casmurro and Memórias Póstumas de Brás Cubas several characteristics of the Brazilian higher education in law in the XIX century, such as its restricted access to the elites, the search for prestige and social differentiation in regard to the rest of the population; and the emphasis on a humanistic culture, disconnected from the practical world of work - done by the slaves -, which was also characterised by a highly sophisticated rhetoric an eloquence in its form, articulated in order to achieve ostentation, in spite of the fact that it was empty in terms of contents. The culture of the elites, in which the higher education in law played a central role, was not related to the progress of the country, but to the perpetuation of the these own groups opression.